Pirfenidone for the treatment of interstitial lung disease associated to rheumatoid arthritis: a new scenario is coming?. (2020) - Cassone, Giulia; Sebastiani, Marco; Vacchi, Caterina; Cerri, Stefania; Salvarani, Carlo; Manfredi, Andreina
Abstract: Introduction: Interstitial lung disease (ILD) is a frequent extra-articular manifestation of Rheumatoid arthritis (RA), but nowadays there are no randomized controlled clinical trials to support therapeutic guidelines. RA-ILD, especially with UIP pattern, shares some similarities with idiopathic pulmonary fibrosis, suggesting a possible role of antifibrotic therapy in these patients. To date, there are no published data supporting the use of pifenidone in RA-ILD. We describe for the first time two patients with a diagnosis of RA-ILD successfully treated with hydroxychloroquine and pirfenidone, without adverse events. Case presentation: Patient 1 and patient 2 were first diagnosed with IPF (UIP pattern at high-resolution computed tomography, no other signs or symptoms suggesting other forms of ILD, routine laboratory examinations and immunological texts negative). Patients started pirfenidone 2403 mg daily. Few months later, they referred to our multidisciplinary outpatient for arthritis. ACPA and RF were positive. A diagnosis of RA was performed and treatment with corticosteroids and hydroxychloroquine was started, in association with pirfenidone. In both cases we assessed the stabilization of articular and lung manifestations, without adverse events. Discussion: In absence of randomized controlled trials, the optimal treatment of RA-ILD has not been determined and remains challenging. When considering therapeutic options for RA-ILD, both pulmonary and extra-thoracic disease manifestations and degrees of activity should be assessed and taken into consideration. Future prospective research might change RA-ILD management, moving to a more personalized approach based on the identification of different phenotypes of the disease or to a combination of immunosuppressive and antifibrotic treatment. Highlights: Nowadays there are no randomized controlled clinical trials to support therapeutic guidelines in RA-ILD. RA-ILD shares some similarities with IPF, suggesting a possible role of antifibrotic therapy RA-ILD patients. We describe for the first time two patients with RA-ILD successfully treated with hydroxychloroquine and pirfenidone. A number of trials are ongoing to assess the efficacy/safety of pirfenidone in fibrosing ILDs other than IPF. To date, multidisciplinary approach in RA-ILD patients remains mandatory.